2014
DOI: 10.1002/jnr.23451
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and A‐317491 depress the transmission of pain on primary afferent mediated by the P2X3 receptor in rats with chronic neuropathic pain states

Abstract: P2X is a family of ligand-gated ion channels that act through adenosine ATP. The P2X3 receptor plays a key role in the transmission of neuropathic pain at peripheral and spinal sites. Electroacupuncture (EA) has been used to treat neuropathic pain effectively. To determine the role of EA in neuropathic pain mediated through the P2X3 receptor in dorsal root ganglion neurons and the spinal cord, a chronic constriction injury (CCI) model was used. Sprague-Dawley rats were divided into four groups: sham CCI, CCI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…These results suggest that P2Y receptors may also play an important role in the development of neuropathic pain [17]. Among P2X and P2Y receptors, many studies revealed that P2X2 and P2X3 receptors have a substantial contribution to ATP-mediated nociception [7,9], and A-317491, the first non-nucleotide antagonist blocking P2X3 homomeric and P2X2/3 heteromeric channels, has been shown to be antinociceptive in rat models of neuropathic pain [27,28]. In addition, a selective P2X7 receptor antagonist A-740003 has also been reported to reduce neuropathic pain in the rat [29].…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest that P2Y receptors may also play an important role in the development of neuropathic pain [17]. Among P2X and P2Y receptors, many studies revealed that P2X2 and P2X3 receptors have a substantial contribution to ATP-mediated nociception [7,9], and A-317491, the first non-nucleotide antagonist blocking P2X3 homomeric and P2X2/3 heteromeric channels, has been shown to be antinociceptive in rat models of neuropathic pain [27,28]. In addition, a selective P2X7 receptor antagonist A-740003 has also been reported to reduce neuropathic pain in the rat [29].…”
Section: Discussionmentioning
confidence: 98%
“…P2X receptors are widely distributed in the body, and they play an important role in the formation, transduction, and regulation of neuropathic pain, inflammatory pain, and visceral pain [17][18][19][20]. Many studies have shown that purinergic (P2X) receptors are involved in pain signal transmission, in which the P2X 3 and P2X 2/3 receptors are the main subtypes [21,22]. Therefore, when studying the pathogenesis of IBS, it is necessary to investigate the relationship between the P2X receptor and IBS visceral hypersensitivity at various levels of the brain-gut axis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanism underlying analgesia of EA at low frequency in PDN remains unclear. Previous studies showed that EA had downregulatory effects on PKC and P2X3 receptor in other animal models [26][27][28]. Thus, the present study aimed to investigate the effects of 2-Hz EA on DRG PKC and P2X3 receptor and whether PKC regulates P2X3 receptor, which may be involved in EA analgesia in PDN.…”
Section: Introductionmentioning
confidence: 99%